Behavioral Adaptation in Children with Down Syndrome: Exploring Perceptual Discrepancies During Early Special Education Transitions - Istiarsyah Istiarsyah; Sauva Yarda; Yoong Soo May; Riki Taufiki; Fahmy Ulfah Mawaddah (Atfaluna: Journal of Islamic Early Childhood Education, 2026)
Purpose – This study examines why behavioral adaptation in children with Down Syndrome during the early transition to special education is difficult to evaluate, addressing the problem that school-readiness judgments often rely on a single informant. It argues that adaptation is context-dependent and that aligning home and school perspectives is essential for accurate assessment and timely intervention.Design/methods/approach – A qualitative collective (multiple-case) study was conducted with a purposive sample of two parent-child dyads and their two classroom teachers at a state special education institution, representing two transition phases: an active early transition and a longer, retrospective one. Data were gathered through semi-structured in-depth interviews, intensive classroom observations, and school documentation, and analyzed using the Miles and Huberman interactive model (data reduction, data display, and conclusion drawing).Findings – Behavioral adaptation was highly context-dependent. Parents perceived marked growth in functional independence and social engagement at home, whereas teachers observed persistent emotional dysregulation, high dependency, and limited cognitive engagement within the structured classroom. This produced a pronounced divergence between parental and teacher perceptions, driven by differing environmental demands and relational familiarity, indicating that readiness cannot be captured through unilateral assessment. Research implications/limitations – As a small-scale qualitative inquiry involving two dyads at a single site, with one case examined retrospectively, the findings offer transferable conceptual parameters rather than statistical generalizability across broader demographic sectors.Practical implications – The results provide foundational benchmarks for early childhood educators to design targeted early intervention programs and adaptive behavior stimulation that align with special-school expectations, thereby mitigating transitional friction and supporting multi-informant, cross-contextual readiness evaluation. Originality/value – The study contributes a cross-contextual, multi-informant lens on school readiness for children with Down Syndrome, foregrounding parent–teacher perceptual discrepancy as a critical assessment factor. Future research should employ larger, multi-site, and longitudinal designs.